If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + -1)(w + -1) = 0 Reorder the terms: (-1 + w)(w + -1) = 0 Reorder the terms: (-1 + w)(-1 + w) = 0 Multiply (-1 + w) * (-1 + w) (-1(-1 + w) + w(-1 + w)) = 0 ((-1 * -1 + w * -1) + w(-1 + w)) = 0 ((1 + -1w) + w(-1 + w)) = 0 (1 + -1w + (-1 * w + w * w)) = 0 (1 + -1w + (-1w + w2)) = 0 Combine like terms: -1w + -1w = -2w (1 + -2w + w2) = 0 Solving 1 + -2w + w2 = 0 Solving for variable 'w'. Factor a trinomial. (1 + -1w)(1 + -1w) = 0Subproblem 1
Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1Subproblem 2
Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1Solution
w = {1, 1}
| 1/2ms | | X-x^2=42 | | 16-1/3x=11 | | 2/5sm | | 13x^2-840x-5040=0 | | 3(w-6)-5w= | | R(1-DT)=D | | -5x+8=3-4x | | 2/3x-84 | | 17-1/3x=11 | | x(x+6)=(x+3)2 | | 56t+62t=42 | | 6(x+3)+2=-16 | | 25x-8-16x+3=25x-4-16x+13 | | %nbsp;= eg;[3] | | -6-y=13 | | x^2+2.4x+1.44=0 | | 22=-7v+5(v+6) | | f(x)=x^2+3(4x)+17 | | (5x+3)(6x^2+8x+9)=0 | | f(x)=1000(.04-x^2) | | -x+12=17 | | 12k-[4k+(-4+2k)]=0 | | x^4+x^3+30x^2-44x=22 | | 7(x+2)+9=-19 | | 100+2x+y+5x+y=180 | | 3=y/8-10 | | 8.00(x+4.00)=72 | | 5x-6+19x=22 | | 3x-2+3x+5+6x-3=180 | | x^2+3xy-2y^2+4=0 | | (2x+7y-4z)-(3x+3y-6z)= |